Qualidade de filés de tilápia alimentadas com pigmentante de origem bacteriana: Thiago Luís Magnani Grassi. - - Grassi, Thiago Luís Magnani [UNESP] (2014)
The reddish hue of some fish acts as a distinctive factor from traditional white flesh, adding value to the product and providing a new product to consumer market. Because of that, the investigation on pigmenting sources for the diets of fish with economic importance is a matter of great interest for aquaculture and food industry. The aim of this work was to evaluate the effects of different carotenoids sources in tilapia fish diets on animals' performance and fillets characteristics. Nine hundred sixty tilapias (Oreochromis niloticus) weighing 10 - 30 g were distributed in 24 tanks and, after an adaptation time, they received the experimental diets for 80 days. Treatments consisted of one control group receiving a basal diet with no pigment, one group receiving asthaxanthin and four groups receiving different concentrations of Rubrivivax gelatinosus biomass as the pigmenting ingredient. Variables analyzed included feed consumption, weight gain and feed conversion for the animals and pH, proximate composition, carotenoids content and color for the fillets. Productive parameters did not differ statistically, showing that the use of the pigments did not cause any damage to animals' performance. Moisture contents of the fillets from the groups that received pigments were lower than those in the fillets from control group, what represents an important factor for the product conservation. The protein contents of the fillets from diets supplemented with the bacterial biomass were higher than those in control group while pH, ash and lipids did not vary among treatments. Lightness and yellowness did not differ among the groups but redness and carotenoids contents were higher for the fillets from all groups that received the pigments than for the control group. So, it can be concluded that the use of the pigmenting ingredients did not alter productive parameters but increased...(Complete abstract eletronic access below)